The pattern of collective memory denial experienced by the student victims’ mothers of 1998-1999 Trisakti-Semanggi Tragedy - Rizqy Amelia Zein; Ilham Nur Alfian (Masyarakat, Kebudayaan dan Politik, 2018)
This research aimed to uncover collective memory denial of the victims’ families of Students who died in Trisakti and Semanggi Tragedy 1998-1999. We described how this pattern of collective memory denial works. This research used the qualitative approach to the instrumental case study. The participants were three mothers of students who died in Trisakti and Semanggi tragedy. We carried out interviews and field note as data collecting technique. This data was analysed using thematic analysis technique. The result showed that there is a denial of collective memory which is experienced by victims’ families of students who died at Trisakti and Semanggi tragedy. The pattern is formed systematically, orderly, and deliberately. This denial showed that the government deliberately prevented the people to remember this tragedy. Collective memory denial causes so many negative effects, such as conspiracy of silence on the people and second victimization for victims’ families. Moreover, these effects included the form of prejudice, mistrust, aversion, and vengeance between the people. When social sharing continuously assembles, it will finish the emotional problem of a negative event. On the other hand, social sharing will develop subjective well-being of the people in that community, not only in short-term but also in long-term. Collective memory which is healthy distributed, motivates the community to discuss, express, and cope the painful trauma in the past.